Clinical Practice Guidelines for Severe Asthma Treatment. - Eddy Pereira Valdes; Moisés Santos Peña; Belkys Rodríguez Llerena (Medisur)
Clinical Practice Guidelines for Severe Asthma Treatment. This disease is characterized by an overreaction of the tracheobronchial tree with hyperactivity after certain stimulus consisting of a diffuse narrowing of the respiratory ways related with an excessive contraction of the bronchial smooth muscle, hyper-secretion of mucus and mucosa edema. It is spontaneously reversible or reversible after treatment. We include a review of its definition, classification and development, stressing those elements related with ventilation. It includes assessment guidelines focused on the most important aspects to be accomplished.